INTEGRATING THE PENTAHELIX APPROACH INTO HUMAN RESOURCE DEVELOPMENT TO PROMOTE SUSTAINABLE ORGANIZATIONAL PERFORMANCE AND ACCELERATE SDGS ACHIEVEMENT - Agustina, Vivi; Nurrohman, Rosyid (Universitas Negeri Gorontalo, 2026)
Purpose This research analyzes the implementation of the pentahelix approach in Human Resource Management Development strategies in village government. The primary focus is on improving the sustainable performance of village officials to support the achievement of the SDGs in villages. The novelty of this research lies in the application of the pentahelix approach to village governance by integrating HRD and sustainable performance. This approach differs from previous research, which generally focuses on the industrial, tourism, or urban sectors. Methods This research uses a qualitative case study approach. Data were obtained from primary and secondary sources and analyzed descriptively using NVivo software for qualitative data management. A SWOT analysis was conducted to identify strengths, weaknesses, opportunities, and threats in the implementation of a pentahelix-based HRD strategy. Finding This research applies the pentahelix approach to village governance by integrating HRD and sustainable performance. This approach differs from previous research, which generally focused on the industrial, tourism, or urban sectors. This research has limitations in the use of a single case study, which limits the generalizability of the findings, and the remote location, which limits the frequency of field visits. Practically, this study recommends a pentahelix approach as a strategy for developing village apparatus human resources and enhancing skills. Further research is recommended using a comparative approach between villages or quantitative methods to measure the impact of the pentahelix approach on sustainable performance and the achievement of the village SDGs.